THE IMPLEMENTATION OF DEBATE TECHNIQUE IN TEACHING ENGLISH SPEAKING TO THE THIRD YEAR STUDENTS OF SMA N 3 SALATIGA - SUMARTINI, TRI (2011)
This research aims at describing the implementation of debate in teaching English speaking to the third year students of SMA N 3 Salatiga. The objectives of this research are to describe the procedure of teaching speaking using debate and the strengths and weaknesses of debate technique implementation. The writer uses descriptive qualitative study that uses method of observation, interview, document and questionnaire. The subject of this research is the students of Language Class at the third year in SMA N 3 Salatiga. The result of the research shows that the procedures of teaching speaking using debate are pre-speaking, whilst-speaking, post-speaking, and closing the lesson. The strengths of debate implementation are students enjoyed and are motivated. They find challenging to be able to think smart, more active, and more creative. The weaknesses of debate implementation are a difficulty to manage the class to make students active and the student’s lack of vocabulary. They are difficult to share their argument or opinion directly. Their arguments are only stored in their mind even they know what they want to say. They need much time to speak up and it takes time.